Pelatihan Klasifikasi Arsip Keluarga Berbasis Digital Sebagai Upaya Siaga Bencana di Desa Pemenang Timur: Pelatihan Klasifikasi Arsip Keluarga Berbasis Digital Sebagai Upaya Siaga Bencana di Desa Pemenang Timur - Hirma, Hirma Susilawati; Nurul Fikriati Ayu Hapsari; Zahwa A’iatul Zaharani; Atika Sumaya (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2025)
Archives are important documents that are inseparable from daily life, ranging from the smallest scope, such as family archives, to larger-scale archives owned by every nation. This community service activity focused on digital-based family archive classification training as a disaster preparedness effort in Pemenang Timur village. The training targeted housewives to enhance their ability to manage family archives so that these important documents can be preserved in the event of sudden natural or human-induced disasters. The objective of this program is to raise public awareness about the importance of managing family archives, which, if poorly managed, can cause problems in the future. This village was previously affected by an earthquake that destroyed residents' homes, resulting in the loss of many important documents. This community service initiative also aims to educate participants on the importance of classifying archives according to their subject, thereby facilitating easier retrieval. The methods used in this activity include outreach, discussions, and practical exercises on digital family archive classification. The activity was carried out in three stages: planning, implementation, and reporting. The planning stage involved observation and coordination with the village authorities as community service partners. In the implementation stage, the village authorities disseminated the information to members of the PKK women's group and health volunteers, who were the primary participants.The results of this program include the successful dissemination of information related to digital information literacy, such as the importance of document management in families, how to distinguish types of family archives—since most participants stored all documents together without categorization—and how to use specific applications to store important family documents. This activity raised awareness among housewives that managing family archives according to classification makes it significantly easier to retrieve documents when needed.